2022
DOI: 10.1177/11771801221118950
|View full text |Cite
|
Sign up to set email alerts
|

A consistent definition of cultural safety within Australian health professional education: a scoping review

Abstract: This scoping review aims to explore how cultural safety is defined in the Australian literature with health professional learners in clinical interactions. It maps how the components of the Australian Health Practitioner Regulation Agency definition of cultural safety align with this evidence. Databases were systematically searched for original, peer-reviewed research that included Australian Aboriginal and Torres Strait Islander peoples, health professional learners who were eligible for registration in Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In the context of culturally safe care this is an important aspect of the Human Library activities. Cultural safety builds on awareness and sensitivity and requires a continual process of reflection on practice with the health professional reflecting on their own cultural identity and privilege ( 4 , 40 , 41 ). Reflective tasks are therefore built into the educational element of the Human Library as mandatory submitted pass/fail tasks, but were not part of the research analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of culturally safe care this is an important aspect of the Human Library activities. Cultural safety builds on awareness and sensitivity and requires a continual process of reflection on practice with the health professional reflecting on their own cultural identity and privilege ( 4 , 40 , 41 ). Reflective tasks are therefore built into the educational element of the Human Library as mandatory submitted pass/fail tasks, but were not part of the research analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Questions are rightly asked about whether cultural competency training and assessment are performed from the perspective of an empowered care provider interacting with an othered client. A scoping review found many elements of cultural safety programs “lacked Indigenous input and had no patient involvement” 19 and this creates numerous mechanisms for potential inadvertent harm, 20 as the scenario demonstrates. Consequently, although there are now some formal mechanisms by which the collective voices of Indigenous patients are being presented, we still lack evidence that health care systems are actually responding to these voices: only four of the 17 Closing the Gap targets are on track, 21 the AIHW reports mixed trends in health system performance, 11 and there is a paucity of data to support a conclusion that “culturally competent” medical professionals are associated with positive health outcomes for Indigenous patients 22 …”
Section: Are Health Care Systems Responsive To Indigenous Australians?mentioning
confidence: 99%
“…Australian initiatives to address Indigenous healthcare are gaining political momentum , with regulatory mandates for cultural safety within health professional training (Brumpton et al, 2022). Indigenous worldviews raise questions about traditional power dynamics within healthcare, where clinicians have been considered as "experts" and patients as "passive recipients" (McWhinney, 1984).…”
Section: Healthcare Improvementmentioning
confidence: 99%